Pelatihan Perawatan Luka Modern Bagi Keluarga Untuk Mencegah Infeksi Di Rumah - Suaib Suaib; Siska Wijayanti Pratiwi; Radiah Ilham; Rachmat Ramli (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Improper wound care at home can increase the risk of infection and slow the healing process. Families play a crucial role in wound care, especially for patients with chronic wounds or those following medical procedures. Modern wound care emphasizes the principles of hygiene, appropriate dressing use, and infection prevention. This Community Service activity aims to improve families' knowledge and skills in implementing modern wound care to prevent infection at home. Implementation methods included counseling, demonstrations, hands-on practice, and evaluation through pre- and post-tests. The results of the activity demonstrated an increase in families' knowledge and skills in performing safe wound care in accordance with modern principles. This training is expected to reduce the risk of wound infection and improve the quality of wound care at home.